2019
DOI: 10.1159/000504577
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Neurotrophin Levels and Their Impact on the Symptoms of Schizophrenia

Abstract: <b><i>Introduction:</i></b> Vitamin D is involved in brain development and functioning, as well as in regulation of neurotrophic factors. Changes in the expression of those factors are possibly responsible for morphologic abnormalities and symptoms in patients suffering from schizophrenia. <b><i>Objective:</i></b> The main goal of this research was to investigate the interrelationship between vitamin D, nerve growth factors (NGF, brain-derived neurotrophic factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…A hypothesis that may explain improvement of NAC parameters in present study is action of VD in regulation of neurotrophin (47). This mechanism has been described in several neurological conditions (48) and the presence of VD receptors on neurons and glia cells (49) reinforce that proposition.…”
Section: Discussionsupporting
confidence: 81%
“…A hypothesis that may explain improvement of NAC parameters in present study is action of VD in regulation of neurotrophin (47). This mechanism has been described in several neurological conditions (48) and the presence of VD receptors on neurons and glia cells (49) reinforce that proposition.…”
Section: Discussionsupporting
confidence: 81%
“… 105 , 106 Two studies failed to find such an association. 97 , 104 One of these studies was substantially larger than all other observational studies. 97 There were no intervention studies testing the use of VIT-D in individuals with schizophrenia.…”
Section: Vitamin D and Serious Mental Disordersmentioning
confidence: 99%
“…There have been six observational studies published since the most recent meta-analysis. 96 , 97 , 104 107 Four studies found a low VIT-D concentration in individuals with psychosis or schizophrenia, 96 , 105 107 two of which concerned first episode psychosis. 105 , 106 Two studies failed to find such an association.…”
Section: Vitamin D and Serious Mental Disordersmentioning
confidence: 99%
“…Considerable evidence shows that neuregulin-(NRG-) 1 plays an important role in regulating the myelination process [21]. Furthermore, clinical [22] and animal studies [23] indicate a critical role of NRG-1 in the development of schizophrenia. Thus, we speculated that NRG-1 was a potential target for the therapeutic effect of SZASD on schizophrenia.…”
Section: Introductionmentioning
confidence: 99%